Model of Tafsir Bi Al-Ma’tsur Approach Relevance to Islamic Education: a Chronological Review of Qur'anic Interpretation - Achmadin, Balya Ziaulhaq; Fattah, Abdul; Alfa, Mohammad Asrori; Mukhsin, Akhmad (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2024)
This study aims to analyze the methods and approaches in tafsir bi al-ma’tsur (tafsir based on history) in a chronological review of the history of Qur'anic interpretation. Tafsir of the Qur'an is a very important discipline in understanding the meaning and message contained in the sacred text of the Qur'an. In this study, we will look at the development of methods and approaches used in tafsir bi al-matsur, which refers to interpretation based on history and tradition. The research method used is a historical approach and literature analysis. The study involves collecting data from various primary and secondary sources, including classical and contemporary books of tafsir, as well as historical literature on Qur'anic interpretation. The collected data will be analyzed chronologically to see the evolution of methods and approaches in tafsir bi al-matsur over time.The results of this study are expected to provide a better understanding of the development and variation of methods and approaches in tafsir bi al-matsur throughout the history of Qur'anic interpretation. In a chronological overview, this study will identify and analyze the different approaches used by mufasirs from different periods, as well as the factors that influenced the changes. It can also provide a foundation for further research in this area, as well as contribute to studies on the history of Qur'ānic interpretation and the development of methods and approaches in tafsir bi al-matsur. With a better understanding of the history and tradition of Qur'ānic interpretation, we can enrich our understanding of the Qur'ānic messages and apply them relevantly in the context of evolving times.Penelitian ini bertujuan untuk menganalisis metode dan pendekatan dalam tafsir bi al-matsur (tafsir berdasarkan sejarah) dalam tinjauan kronologis sejarah penafsiran Al-Qur'an. Tafsir Al-Qur'an merupakan disiplin ilmu yang sangat penting dalam memahami makna dan pesan yang terkandung dalam teks suci Al-Qur'an. Dalam kajian ini akan melihat perkembangan metode dan pendekatan yang digunakan dalam tafsir bi al-matsur yang mengacu pada penafsiran berdasarkan sejarah dan tradisi. Metode penelitian yang digunakan adalah pendekatan sejarah dan analisis literatur. Kajian ini melibatkan pengumpulan data dari berbagai sumber primer dan sekunder, termasuk kitab-kitab tafsir klasik dan kontemporer, serta literatur sejarah tentang tafsir Al-Qur'an. Data yang terkumpul akan dianalisis secara kronologis untuk melihat evolusi metode dan pendekatan dalam tafsir bi al-matsur dari waktu ke waktu. Hasil penelitian ini diharapkan dapat memberikan pemahaman yang lebih baik mengenai perkembangan dan variasi metode dan pendekatan dalam tafsir bi al-matsur. matsur sepanjang sejarah penafsiran Al-Qur'an. Secara kronologis, penelitian ini akan mengidentifikasi dan menganalisis berbagai pendekatan yang digunakan para mufasir dari berbagai periode, serta faktor-faktor yang mempengaruhi perubahan tersebut. Hal ini juga dapat memberikan landasan bagi penelitian lebih lanjut di bidang ini, serta memberikan kontribusi terhadap kajian tentang sejarah penafsiran Al-Qur'an dan pengembangan metode dan pendekatan dalam tafsir bi al-matsur. Dengan pemahaman yang lebih baik terhadap sejarah dan tradisi penafsiran Al-Qur'an, kita dapat memperkaya pemahaman kita terhadap pesan-pesan Al-Qur'an dan menerapkannya secara relevan dalam konteks perkembangan zaman.